Enhancing Pedagogical Competence of Pre-Service Islamic Education Teachers through Peer Assessment and Constructive Feedback - Amrullah, Amrullah; Apriani, Eka; Idris, Muhammad (Jurnal Pendidikan Islam, 2025)
Purpose – This study aims to analyze the influence of peer assessment and constructive feedback on the pedagogical skills of Islamic Education pre-service teachers in the microteaching course. Design/methods/approach – This research employed a quantitative design with a correlational explanatory approach. The study population consisted of two classes of sixth-semester students from the Islamic Education Study Program at the State Institute for Islamic Studies (IAIN) Curup, all of whom were enrolled in the microteaching course. The data were analyzed using multiple linear regression to assess both the simultaneous and partial effects of the two independent variables on the dependent variable. Findings – The F-test showed a value of 24.173 with a significance of 0.000 (p < 0.05), indicating that peer assessment and constructive feedback together significantly affect students' pedagogical skills. The t-test results revealed that peer assessment (t = 3.052, p = 0.004) and constructive feedback (t = 3.762, p = 0.000) each have a significant individual impact (p < 0.05), confirming their respective contributions to improving pedagogical skills. Research implications – Pedagogical skills are essential for prospective teachers, especially in improving their understanding and teaching skills. Although microteaching offers practical teaching experience, students still face challenges in areas such as lesson planning, classroom management, teaching strategies, and assessment. To address these issues, peer assessment and constructive feedback offer promising strategies to enhance pedagogical development.